2021
DOI: 10.1097/meg.0000000000001969
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, incidence and clinical features of SARS-CoV-2 infection in adult coeliac patients

Abstract: Objectives Data on SARS-CoV-2 disease (COVID-19) in adult coeliac disease (CD) are lacking. The aim of the present study is to evaluate the epidemiology and clinical features of COVID-19 in adult coeliac patients regularly followed-up at our centre since January 2015. Methods Data about general health status and clinical features of laboratory-confirmed COVID-19 were prospectively collected over the phone. Data about CD were retrospectively collected from clinical notes. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 27 publications
(46 reference statements)
2
28
0
Order By: Relevance
“…Surprisingly, coeliac patients tended to have higher antibody titers than controls at all time points, although this difference only reached statistical significance at 6 months. These results are in line with recent studies on risk of contracting COVID-19 in coeliac patients, which did not find an increased risk of COVID-19 or of severe COVID-19 disease in coeliac patients compared to the general population [19][20][21][22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Surprisingly, coeliac patients tended to have higher antibody titers than controls at all time points, although this difference only reached statistical significance at 6 months. These results are in line with recent studies on risk of contracting COVID-19 in coeliac patients, which did not find an increased risk of COVID-19 or of severe COVID-19 disease in coeliac patients compared to the general population [19][20][21][22].…”
Section: Discussionsupporting
confidence: 92%
“…It has recently been shown that coeliac patients are not at increased risk of contracting COVID-19 compared to the general population and that their disease course is usually mild [19][20][21][22]. To date, there is no data on the serological response to vaccination against SARS-CoV-2 in patients affected by coeliac disease and NCE.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary data from the International Coronavirus and Celiac Disease Reporting Database showed that CD serology and adherence to a gluten-free diet (GFD) were not associated with severe outcomes [ 9 ]. These results were confirmed by subsequent studies, which did not find a correlation between COVID-19 and CD, reporting a similar clinical course in celiac and nonceliac patients, especially in those compliant with the GFD [ 10 , 11 ].…”
Section: Introductionsupporting
confidence: 70%
“…Recent studies demonstrated that patients with inflammatory bowel disease (IBD) have no risk or are at low risk of developing COVID-19 [ 18 ]. Similarly, patients with CD do not seem to have an increased risk of COVID-19 compared with the general population, and, if infected, their disease course is similar to that of the general population [ 11 ]. However, the COVID-19 pandemic has had a major effect on pediatric gastroenterology practice [ 19 ], and a potentially life-threatening delay in the diagnosis of celiac disease was also reported in a young child [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CD do not bear a risk of COVID-19 correlated to the general population, and their disease line was mild. Clinical type of CD, age, sex, duration, and adherence to a GFD, and mucosal healing did not differ between CD patients with and without COVID-19 [ 55 ]. But the restrictions applied to COVID-19 can impact CD treatment and GFD, the only available therapy for CD [ 56 ].…”
Section: Suggested Causes For the Recent Increase In CD Incidencementioning
confidence: 99%